2018
DOI: 10.1101/369876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of 10-valent pneumococcal conjugate vaccine on invasive pneumococcal disease and nasopharyngeal carriage in Kenya

Abstract: Background: 10-valent pneumococcal conjugate vaccine (PCV10), delivered at 6, 10 and 14 weeks of age, was introduced in Kenya in January 2011, accompanied by a catch-up campaign in Kilifi County for children <5 years. Coverage with ≥2 PCV10 doses in children 2-11 months was 80% in 2011 and 84% in 2016; coverage with ≥1 dose in children 12-59 months was 66% and 87%, respectively. Methods: Clinical and microbiological surveillance for invasive pneumococcal disease (IPD) among admissions of all ages at Kilifi Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
(39 reference statements)
1
12
2
Order By: Relevance
“…Kenya reported a reduction from 34% to 9% VT carriage among PCV-vaccinated children under 5 years of age, 6 years after introduction of 10-valent PCV. 19 The Gambia reported a reduction from 50% to 13% VT carriage among children 2-5 years old, 20 months after introducing the 7-valent PCV. 45 Likewise, a study from South Africa showed reduced PCV13serotype colonisation from 37% to 13% within 1 year of transitioning from PCV7 to PCV13.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kenya reported a reduction from 34% to 9% VT carriage among PCV-vaccinated children under 5 years of age, 6 years after introduction of 10-valent PCV. 19 The Gambia reported a reduction from 50% to 13% VT carriage among children 2-5 years old, 20 months after introducing the 7-valent PCV. 45 Likewise, a study from South Africa showed reduced PCV13serotype colonisation from 37% to 13% within 1 year of transitioning from PCV7 to PCV13.…”
Section: Discussionmentioning
confidence: 97%
“…14 Vaccine trials and post-routine-introduction studies in Africa have demonstrated substantial direct effects of PCV against IPD, pneumonia, and all-cause mortality among young children. [15][16][17][18] Although Kenya, 19 The Gambia, 18 Mozambique 20 , and South Africa 21 have reported VT carriage reductions, residual carriage prevalences are still higher than in industrialised countries. [22][23][24] In addition, there is evidence of rapid onset of NVT replacement in the region.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted IPD incidence by multiplying modelled age-specific carriage incidence with case-to-carrier ratios (CCR). For each model posterior the CCRs were calculated as the ratio of the observed pre-vaccination IPD incidence at Kilifi Country Hospital (KCH) 3 to modelled pre-vaccination carriage incidence. The CCR were assumed to remain unchanged post-vaccination.…”
Section: Methodsmentioning
confidence: 99%
“…Pneumococcal sepsis was defined as IPD not meeting the definitions of pneumococcal meningitis or bacteraemic pneumococcal pneumonia. We further assumed that for every prevented case of IPD one would prevent 5.3 cases of clinically-defined pneumonia 3,6 . This ratio was estimated by dividing the vaccine preventable clinical pneumonia incidence (351 per 100,000 per year) 3 to vaccine preventable IPD incidence (66.3 per 100,000 per year) 6 that were both estimated from surveillance at KCH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation